Too hot to handle: Mood states moderate implicit approach vs. avoidance tendencies toward food cues in patients with obesity and active binge eating disorder - Krehbiel, Johannes; Halbeisen, Georg; Kühn, Simone; Erim, Yesim; Paslakis, Georgios (Journal of Psychiatric Research, 2021)
Patients with binge eating disorder (BED) display recurring episodes of eating large amounts of food in a short period of time, especially during negative mood states. However, the psychological processes linking negative mood to binge eating behavior have not been sufficiently explored. This study investigated the effects of experimentally inducing a negative (sad) mood state upon reaction times in a computerized Approach-Avoidance-Task (AAT) using images of foods and compared to a neutral control procedure in which negative mood was not induced. Differences in reaction times between “pulling” and “pushing away” food cues in the AAT were considered surrogates for fast, automatic (i.e., implicit) preferences (“bias”) for either the approach or avoidance of foods. Obese patients with BED (n = 40), weight-matched (obese) individuals (n = 40), and norm-weight controls (n = 29) were asked to approach (“pull”) or avoid (“push”) images of high- and low-calorie foods following the induction of a negative mood state vs. the neutral control procedure. Sample size was within the common range of previous investigations of the kind. Similar to previous findings, obese patients with BED exhibited an avoidance bias (i.e., faster reaction times in “pushing” compared to “pulling”) during the neutral control condition. However, a contrast analysis revealed that negative mood was associated with decreased avoidance bias in obese patients with BED, but not in obese and norm-weight controls. Mood status exerted no effect on BED patients’ self-reported (i.e., explicit) ratings of the urge to consume foods. These findings may help to advance current understanding of how negative (sad) mood states may affect binge eating behaviors. Implications of these findings for developing novel treatment approaches are discussed.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Approach avoidance task; Binge eating disorder; Eating disorder; Implicit bias; Psychotherapy